TiO2 thin film-based low concentration MIS hydrogen sensor - Shubham K.; Khan R.U.; Chakrabarti P. (My University, 2025)
The present paper deals with a thin film based Pd/TiO2/n-Si MIS hydrogen sensor using Titanium Dioxide (TiO2) as an insulator. The TiO2 thin film has been deposited by using low temperature arc vapor deposition (LTAVD) technique. The gas sensing properties of the MIS structure were studied towards hydrogen (0.1-2 ppm in air) at room temperature and 50°C respectively. The response of the sensor was measured as shift in C-V curve of the MIS structure. The device exhibits better sensitivity to hydrogen at zero gate bias. High sensitivity of the sensor can be attributed to the change of interface state charges on exposure of gases along with the formation of dipole layer. The values of response time as well as the recovery time have also been estimated and found good compared to conventional MOS structure. © 2012 IEEE.